Association of serum KL-6 levels with interstitial lung disease in patients with connective tissue disease: a cross-sectional study - Oguz, Ekin Oktay; Kucuksahin, Orhan; Turgay, Murat; Yildizgoren, Mustafa Turgut; Ates, Askin; Demir, Nalan; Kumbasar, Ozlem Ozdemir; Kinikli, Gulay; Duzgun, Nursen (Clinical rheumatology, 2016)
It was aimed to evaluate KL-6 glycoprotein levels to determine if it may be a diagnostic marker for the connective tissue diseases (CTDs) predicting CTD-related interstitial lung diseases (ILDs) (CTD-ILD) development and to examine if there was a difference between patients and healthy controls. The study included 113 patients with CTD (45 CTD without lung involvement, 68 CTD-ILD) and 45 healthy control subjects. KL-6 glycoprotein levels were analyzed with ELISA in patients and the control group. The relationship between KL-6 glycoprotein levels and CTD-ILD was assessed. In the comparison of all the groups in the study, significantly higher levels of KL-6 were determined in the CTD-ILD group than in either the CTD without pulmonary involvement group or the healthy control group ( p < 0.008 and p < 0.001, respectively). There was no statistically significant difference between the KL-6 levels in the healthy control group and the CTD without pulmonary involvement group ( p = 0.289). The KL-6 levels did not differ significantly according to the connective tissue diseases in the diagnostic groups (systemic lupus erythematosus, Sjögren’s syndrome, rheumatoid arthritis, mixed connective tissue disease, scleroderma, polymyositis/ dermatomyositis). In the healthy control group, there was a statistically significant difference between KL-6 levels in smokers and non-smokers. Smokers had significantly higher serum KL-6 levels compared with non-smokers ( p < 0.05). There was no statistically significant difference between smoking status (pack-year) and serum KL-6 levels. There was no statistically significant correlation between serum KL-6 levels and time since diagnosis of CTD and CTD-ILD. The level of KL-6 as a predictive factor could be used to identify the clinical development of ILD before it is detected on imaging modality. Further prospective clinical studies are needed to define whether levels of KL-6 might have prognostic value or might predict progressive ILD.